Models of evolutionary rescue with plasticity and nonlinear environmental change: code and data - Greenspoon, Philip; Spencer, Hamish (Dryad, 2021)
Rapid environmental changes are putting numerous species at risk of
extinction. For migration-limited species, persistence depends on either
phenotypic plasticity or evolutionary adaptation (evolutionary rescue).
Current theory on evolutionary rescue typically assumes linear
environmental change. Yet accelerating environmental change may pose a
bigger threat. Here we present the simulation code and data from
a model of a species encountering an environment with
accelerating or decelerating change, to which it can adapt through
evolution or phenotypic plasticity (within-generational or
transgenerational). We show that unless either form of plasticity is
sufficiently strong or adaptive genetic variation is sufficiently
plentiful, accelerating or decelerating environmental change increases
extinction risk compared to linear environmental change for the same mean
rate of environmental change.
Please see the "Description_of_data.pdf" file for
description of data.